ECONOMIC IMPACT OF ANTI-LEUKEMIA MEASURES - Ruziev Zokhidzhon Egamberdievich; Ergashev N. N. (Journals Park Publishing, 2022)
In these farms, the economic efficiency of health-improving anti-leukemia measures has been determined, bovine leukemia causes great economic damage to livestock due to death, forced slaughter, reduced productivity of animals with leukemia, lack of milk and offspring, violations of breeding work and requires very high costs for carrying out veterinary and sanitary measures, and carrying out a complex of health-improving anti-leukemia measures helps to prevent damage and increase the economic efficiency of veterinary and sanitary measures
Keywords: leukemia, economic effect, damage, death, milk, offspring, breeding, farming.